Detectable ctDNA at the time of treatment cessation of ipilimumab and nivolumab for toxicity predicts disease progression in advanced melanoma patients - Warburton, Lydia; Reid, Anna; Amanuel, Benhur; Calapre, Leslie; Millward, Michael; Gray, Elin (Frontiers in Oncology, 2023)
Immune checkpoint inhibition (ICI) has led to unprecedented outcomes for melanoma patients. ICI resumption after irAEs poses a challenge in the management of melanoma patients and there are no biomarkers that can help identify patients that benefit from resuming treatment. This study aims to determine if circulating tumour DNA (ctDNA) levels at the time of treatment-limiting irAE could guide decisions. This retrospective exploratory biomarker study (n=34) treated with combination ICI for stageIV melanoma. Patients had treatment-limiting toxicity and baseline plasma collection prior to commencing ICI and within 6weeks of stopping therapy. Blood samples were tested for ctDNA at baseline and cessation therapy. Median progression free survival (PFS) and overall survival (OS) have not been reached (24-mth PFS rate 54 % and OS rate 72.3%). PD occurred in 47% (16/34) Median PFS with detectable ctDNA from plasma at time of toxicity was 6.5months while not reached (NR) with undetectable levels (HR: 4.0, 95% CI 0.95-17.5, p=0.0023). Median OS with detectable ctDNA at cessation for toxicity was 19.4months and NR for undetectable ctDNA (HR: 3.9, 95%CI 20.8-18.6, p=0.024). Positive ctDNA at the time of cessation was highly specific (specificity 0.94, 95% CI 0.74-0.99, PPV 0.88, 95% CI 0.53-0.99). Notably, 4/9 (44%) ctDNA negative patients who had PD had brain only disease progression. Undetectable ctDNA and CR on imaging after stopping for toxicity results in high rates of long-term durable control. For patients with immunotherapy related toxicity, who have persistent ctDNA at 8 – 12 weeks, the risk of disease progression is significant.